10n+4n+(-3n)+2=

Simple and best practice solution for 10n+4n+(-3n)+2= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10n+4n+(-3n)+2= equation:


Simplifying
10n + 4n + (-3n) + 2 = 0

Reorder the terms:
2 + 10n + 4n + (-3n) = 0

Combine like terms: 10n + 4n = 14n
2 + 14n + (-3n) = 0

Combine like terms: 14n + (-3n) = 11n
2 + 11n = 0

Solving
2 + 11n = 0

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-2' to each side of the equation.
2 + -2 + 11n = 0 + -2

Combine like terms: 2 + -2 = 0
0 + 11n = 0 + -2
11n = 0 + -2

Combine like terms: 0 + -2 = -2
11n = -2

Divide each side by '11'.
n = -0.1818181818

Simplifying
n = -0.1818181818

See similar equations:

| 4w-2=35 | | 3u+10=16 | | 0.02x^2-28x+8400=0 | | 276-0.01x^2=0 | | 5=5a-7 | | -x^4+.5x^2+.35x+.525=0 | | i-.7*29=32 | | 9v+7-2(-4v-3)=5(v-1) | | 3*40-x=4+x | | 1/2t=5/2 | | 6x+9=9y-2x | | -2u+-16=2u-9+8u+2 | | 20/9=-4/5x | | [8(3-6)-1]-[4-(6-4)]= | | 5h+8j-8(5h-5j+4k)= | | 4m+2n-3(8m-5n)= | | -10x+4x^3=0 | | 83d-(39d-29)= | | 3*2x+4=7 | | X*3-11=7 | | 4(3q-2)=19q | | 4a^2+20a-24=0 | | (5a)3/5 | | x+97=-7 | | 3and1/10s=6and1/5 | | 4(8-x)-12=7x-6(x-2)-2 | | 0.75-3p=5.88 | | -16x^2+16x+0=3.96 | | -(x-1)=x+1 | | ((ln-5)/(ln3))-5 | | 1000x^3+7000x=18000 | | 9x+13=13(2x-4)+31 |

Equations solver categories